COMPARISON FOR CARICA PAPAYA AND GENGIGEL LEAVES EXTRACTION FOR GINGIVITIS HEALING EFFECTIVENESS IN ORTHODONTIC APPLICATION - Anfasa Isnurhakim; Budi Suhartono; Rama Putranto (Jurnal Medali, 2021)
Background: Gingivitis is the infection disease with tooth loss effect. Using fixed orthodontic appliance in dentistry can give gingivitis impact with its’ designed way. To determine the effectiveness of papaya leaf extraction and gengigel in gingivitis treatment with fixed orthodontic application in letrature review explanation Methods: Literature searching with Science Direct, NCBI (PubMed), and Google Scholar databases and getting 530 articles. Articles are screened to be 67 articles and selected by inclusion and exclusion criteria getting 37 articles. 37 Articles are ready to be analysed. Results:There is effectiveness of papaya leaf extract and gengigel in patients using fixed orthodontic appliances for giving anti inflammation effect, wound healing and enhance blood circulation. Conclusion: The conclusion is papaya and gengigel leaf extraction giving gingivitis healing effect in fixed orthodontic treatment